MicroRNA-22 Induces Endothelial Progenitor Cell Senescence by Targeting AKT3 - Yue Zheng; Zhiwei Xu (Cellular Physiology and Biochemistry, 2014)
Objectives: Endothelial progenitor cells (EPCs) play an important role in postnatal neovascularization. The number and function of EPCs declines as part of aging-associated senescence, thereby potentially contributing to vascular pathologies. Here, we investigated the significance and molecular mechanisms of microRNA-22 (miR-22) governing EPC senescence. Methods: EPCs were isolated from human circulating mononuclear cells from healthy young and aged volunteers. Cell senescence, proliferation, migration and tube formation ability were detected by SA-β-gal staining assay, MTT assay, transwell assay and Matrigel-based angiogenesis assay. Gene and protein expression were analyzed by qRT-PCR and Western blot respectively. Results: We found that miR-22 was upregulated in aged EPCs. Overexpression of miR-22 in young EPCs induced cell senescence, decreased proliferation and migration, and impaired angiogenesis in vitro. Conversely, silencing of endogenous miR-22 led to decreased cell senescence, increased proliferation and migration, and improved angiogenesis. AKT3 was identified as a direct target of miR-22, and restoration of AKT3 expression attenuated the effects of miR-22 in young EPCs. Conclusion: Our results indicate that miR-22 induces EPC senescence by downregulating AKT3 expression, providing a potential novel target for the reversal of EPC dysfunction in angiogenesis.